Gut–Brain Axis: Potential Factors Involved in the Pathogenesis of Parkinson's Disease - Chao, Yin-Xia; Gulam, Muhammad Yaaseen; Chia, Nicholas Shyh Jenn; Feng, Lei; Rotzschke, Olaf; Tan, Eng-King (Frontiers in Neurology, 2020)
Increasing evidence suggests an association between gastrointestinal (GI) disorders and susceptibility and progress of Parkinson's disease (PD). Gut–brain axis has been proposed to play important roles in the pathogenesis of PD, though the exact pathophysiologic mechanism has yet to be elucidated. Here, we discuss the common factors involved in both PD and GI disorders, including genes, altered gut microbiota, diet, environmental toxins, and altered mucosal immunity. Large-scale prospective clinical studies are needed to define the exact relationship between dietary factors, microbiome, and genetic factors in PD. Identification of early diagnostic markers and demonstration of the efficacy of diet modulation and regulation of gut microbiome through specific therapeutics can potentially change the treatment paradigm for PD.